Beispiel Nr: 36
$ \text{Gegeben:} y=ax^2+bx+c \\ \text{Gesucht:} \\ \text{Scheitel und Scheitelform}\\ \text{Definitions- und Wertebereich} \\ \text{Nullstellen - Schnittpunkt mit der x-Achse} \\ \text{Faktorisiere Form} \\ \text{Scheitel} \\ Eigenschaften\\ \textbf{Gegeben:} \\ y= \frac{1}{2}x^2-2x+1\frac{1}{2}\\ \\ \textbf{Rechnung:} \\\bullet \text{Funktion} \\ y= \frac{1}{2}x^2-2x+1\frac{1}{2}\\ \\ \bullet \text{Scheitelberechnung } \\ \begin{array}{l|l|l} \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=\frac{1}{2}x^2-2x+1\frac{1}{2} \\ y=\frac{1}{2}(x^2-4x+3) \\ y=\frac{1}{2}(x^2-4x+2^2-2^2+3) \\ y=\frac{1}{2}[(x-2)^2-2^2+3] \\ y=\frac{1}{2}[(x-2)^2-4+3] \\ y=\frac{1}{2}[(x-2)^2-1] \\ y=\frac{1}{2}(x-2)^2-\frac{1}{2} \\ Scheitel(2/-\frac{1}{2}) \end{array} & \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=\frac{1}{2}x^2-2x+1\frac{1}{2} \\ y=\frac{1}{2}(x^2-4x)+1\frac{1}{2} \\ y=\frac{1}{2}(x^2-4x+2^2-2^2)+1\frac{1}{2} \\ y=\frac{1}{2}[(x-2)^2-2^2]+1\frac{1}{2} \\ y=\frac{1}{2}[(x-2)^2-4]+1\frac{1}{2} \\ y=\frac{1}{2}(x-2)^2-2+1\frac{1}{2} \\ y=\frac{1}{2}(x-2)^2-\frac{1}{2} \\ Scheitel(2/-\frac{1}{2}) \end{array} & \begin{array}{l} \text{Scheitelformel} \\ \hline y=\frac{1}{2}x^2-2x+1\frac{1}{2} \\ xs=-\frac{-2}{2\cdot \frac{1}{2}} \\ xs=2 \\ ys=1\frac{1}{2}-\frac{\left(-2\right)^2}{4\cdot\frac{1}{2}} \\ ys=-\frac{1}{2} \\ Scheitel(2/-\frac{1}{2})\\ y=\frac{1}{2}(x-2)^2-\frac{1}{2} \end{array} \\ \end{array} \\ \\ \\\bullet\text{Definitions- und Wertebereich:}\qquad \mathbb{D} = \mathbb{R} \qquad \mathbb{W} = [(-\frac{1}{2});\infty[ \\ \\=\frac{1}{2}(x-1)(x-3)\\ \\\bullet \text{Nullstellen / Schnittpunkt mit der x-Achse:} \\y= \frac{1}{2}x^2-2x+1\frac{1}{2} = 0 \\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ \frac{1}{2}x^{2}-2x+1\frac{1}{2} =0 \\ x_{1/2}=\displaystyle\frac{+2 \pm\sqrt{\left(-2\right)^{2}-4\cdot \frac{1}{2} \cdot 1\frac{1}{2}}}{2\cdot\frac{1}{2}} \\ x_{1/2}=\displaystyle \frac{+2 \pm\sqrt{1}}{1} \\ x_{1/2}=\displaystyle \frac{2 \pm1}{1} \\ x_{1}=\displaystyle \frac{2 +1}{1} \qquad x_{2}=\displaystyle \frac{2 -1}{1} \\ x_{1}=3 \qquad x_{2}=1 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ \frac{1}{2}x^{2}-2x+1\frac{1}{2} =0 \qquad /:\frac{1}{2} \\ x^{2}-4x+3 =0 \\ x_{1/2}=\displaystyle -\frac{-4}{2}\pm\sqrt{\left(\frac{\left(-4\right)}{2}\right)^2- 3} \\ x_{1/2}=\displaystyle 2\pm\sqrt{1} \\ x_{1/2}=\displaystyle 2\pm1 \\ x_{1}=3 \qquad x_{2}=1 \end{array}\\ \end{array}\\ \underline{x_1=1; \quad1\text{-fache Nullstelle}} \\\underline{x_2=3; \quad1\text{-fache Nullstelle}} \\ \\ \bullet \text{Vorzeichentabelle:} \\ \begin{array}{|c|c|c|c|c|c|c||} \hline & x < &1&< x <&3&< x\\ \hline f(x)&+&0&-&0&+\\ \hline \end{array}\\ \\ \underline{\quad x \in ]-\infty;1[\quad \cup \quad]3;\infty[\quad f(x)>0 \quad \text{oberhalb der x-Achse}}\\ \\ \underline{\quad x \in ]1;3[\quad f(x)<0 \quad \text{unterhalb der x-Achse}}$